THE PORTRAYAL OF INDONESIAN MOTHER IN THE TRANSLATED NOVEL "THE FALL AND THE HEART" BY S. RUKIAH KERTAPATI (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
This paper aims to show how the portrait of an Indonesian mother is shown in the translated novel The Fall and the Heart (1950), written by Siti Rukiah Kertapati, an Indonesian woman writer during the revolutionary era. In addition, this paper also aims to provide an overview of how the characterization of the mother can influence the other family members’ characterizations. This novel tells a story of a small family consisting of a father, mother, and three daughters, namely Dini, Lina, and Susi. The mother is portrayed to have a more dominant role than the father in educating and instilling the values of life to her three daughters. In carrying out her role, the Mother is portrayed to instill female stereotypes into her three daughters. However, the responses of the three daughters are shown differently and bring an impact on each daughter's life story. The present writer uses the theories of characterization, themes, female stereotypes, and also the concept of the mother’s role. The results show that the mother's characterization, which is a round character, has a significant influence on the characters of her husband and her three children. After analyzing how the Mother's character affects the other family members, the writer finds that the portraits of the Indonesian mother shown in the novel are a strong and tenacious character, a dominant character, and a source (giver) of blessing for her children.